Medical Fatwas in the Social Sphere: Toward a Community Legal Framework - Rus Yandi; Yenita Yatim; Basrial Zuhri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This background is based on the increasingly rapid advancement of contemporary medical science, such as DNA-based vaccination and media euthanasia, which have given rise to new bioethical issues not yet explicitly regulated in classical Islamic jurisprudence. In this context, medical fatwas issued by religious institutions serve as the primary reference. However, tensions arise between normative fatwas and social reality. This demonstrates that medical fatwas are not merely legal products, but rather social arenas where various interests, authorities, and negotiations converge among ulama, medical personnel, patients, and the state. This study aims, first, to analyze medical fatwas as a social arena in contemporary Muslim society. Second, to identify social factors influencing the production, dimensions, and acceptance of medical fatwas. Third, to formulate an Islamic legal framework adaptive to medical advancements. The method used is a qualitative approach, designed as a case study of controversial medical fatwas in Indonesia, with data collection conducted through a literature review. The study found that medical fatwas are produced through a process of negotiation between the authority of ulama and medical personnel, often overshadowed by political and economic interests. Restrictive or prohibitive fatwas tend to be less followed if they conflict with the patient's immediate needs, while looser fatwas often trigger resistance from conservative groups. The findings indicate that the most adaptive medical fatwas are those produced through a participatory process, utilizing the maqasid al-Shariah approach, local conditions, and scientific developments. Conclusion: Medical fatwas cannot be understood as normative products, but rather as dynamic arenas. An Islamic legal framework that is adaptive to medical developments can only be realized if the ifta' (fatwa-making) process is inclusive, multidisciplinary, and responsive to the empirical realities of contemporary Muslim society.